The Effectiveness of Aromatherapy and Music Therapy to Reduce Pain during Stage-1 of Birth Delivery: A Meta-Analysis - Hasanah, Uswatun; Murti, Bhisma; Prasetya, Hanung (Journal of Maternal and Child Health, 2021)
Background: Labor pain is an uncomfortable feeling during the labor process, which causes a reduction in uterine contractions,